Privilege and anxiety : the Korean middle class in the global era - Koo, Hagen, 1941- (Cornell University Press, 2022)
"Privilege and Anxiety is about the transformation of the Korean middle class over the past four decades. The Korean middle class grew rapidly during the period of industrial development and provided a social base for the political stability and democratic transition in the 1980s. But it began to decline abruptly from the mid-1990s and is now widely believed to be in deep economic and social crisis. Hagen Koo argues that, rather than focusing on the shrinking size of the middle class and the rise of a distinctly inegalitarian society, the more significant change to the middle class is actually qualitative, namely that the Korean middle class has transformed from a relatively homogeneous, fluid, and upwardly mobile class into an internally divided, fractured, and anxiety-ridden class."--